Synergie zwischen priesterlichem und göttlichem Handeln im Aaronitischen Segen (Num 6,22-27): Ein Beitrag zum Verständnis der Wendung yishaׂʾ yehṿah fanayṿ ʾeleykha - Geiger, Michaela (Vetus Testamentum, 2018)
The expression (יִשָּׂא יְהוָה פָּנָיו אֵלֶיךָ Num 6,26) is unique in the Hebrew Bible and has not been fully explained yet. This article suggests that the preposition (אֶל Num 6,25.26) is the key to understanding, since it links Num 6,24-26 to Lev 9,22-24 (3 times אֶל) as well as to the framing verses Num 6,22f.27 (3 times אֶל). Semantical, redaction- and tradition-critical analyses prompt that the expression יִשָּׂא יְהוָה פָּנָיו אֵלֶיךָ was created especially for the priestly blessing to evoke the imagination of being received before the divine king. The preposition אֵלֶיךָ in Num 6,25.26 emphasizes the relationship between God and the blessed individuals and alludes to the expression וַיִּשָּׂא אַהֲרֹן אֶת־יָדוֹ אֶל־הָעָם וַיְבָרְכֵם in Lev 9,22: the priest’s gesture of blessing allows to perceive the presence of God. The liturgical formula was finally included into the Sinai pericope by a postpriestly redaction, along with the framing verses Num 6,22f.27.